An incentive pricing mechanism for efficient airport slot allocation in Europe. (January 2015) - Avenali, Alessandro; D'Alfonso, Tiziana; Leporelli, Claudio; Matteucci, Giorgio; Nastasi, Alberto; Reverberi, Pierfrancesco
Abstract: We define a supervised market mechanism to deal with the airport slot allocation problem. This mechanism is based on the principles underlying the AIP model for regulation of radio spectrum. Incentive prices for airport slots should reflect an estimate of the marginal value of each slot to end users. We compute this value by assessing the downgrade in the provision of the air transport service, both in terms of quantity (i.e. number of transported passengers) and quality (i.e. passenger travel times), should access to any given slot be denied. Incentive prices consider interdependencies among slots at different airports. We argue that, in principle, incentive prices may better align private and social decisions over the use of slots compared with the outcomes of pure market interactions (such as auctions and trading). Highlights: We provide an incentive pricing mechanism for airport slot allocation. We consider slot capacities and interdependencies among slots in the airport network. We build incentive prices on a measure of the best use of slots in serving end users. Incentive prices ensure the recovery of efficient costs of supplying all slots. Pure market mechanisms may yield inefficient slot allocations due to market failures.